Microflow photochemistry: UVC-induced [2 + 2]-photoadditions to furanone in a microcapillary reactor - Bachollet, Sylvestre; Terao, Kimitada; Aida, Shin; Nishiyama, Yasuhiro; Kakiuchi, Kiyomi; Oelgemöller, Michael (Beilstein Journal of Organic Chemistry, 2013)
[2 + 2]-Cycloadditions of cyclopentene and 2,3-dimethylbut-2-ene to furanone were investigated under continuous-flow conditions. Irradiations were conducted in a FEP-microcapillary module which was placed in a Rayonet chamber photoreactor equipped with low wattage UVC-lamps. Conversion rates and isolated yields were compared to analogue batch reactions in a quartz test tube. In all cases examined, the microcapillary reactor furnished faster conversions and improved product qualities.
Keywords: cycloaddition; cyclobutane; flow chemistry; furanone; microflow chemistry; photochemistry